(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The Arabian Peninsula has been subject to Ottoman occupation since the sixteenth century AD, but the Ottoman presence there was subjected to violent tremors during the first Ottoman era.The Ottoman forces left Yemen after the revolution of its people in 1635, and the Ottoman rule collapsed in Al-Ahsa and eastern Arabia in 1670.To a purely nominal sovereignty and influence moved to the Sharif of Mecca, in addition to that the Ottoman Empire did not control during the first Ottoman era the center of the Arabian Peninsula, and the Sublime Porte contented itself with the exercise of nominal sovereignty over the tribes of Najd and Shammar. Britain found in the decline of the Ottoman influence in the Arabian Peninsula an opportunity to penetrate the Arabian Gulf. Therefore, it has given this region great attention since the seventeenth century, for economic, political and military motives, which are extremely important factors at all times in relation to the British strategy.Britain was able to get rid of all its European competitors in the Persian Gulf, but the nineteenth century witnessed a strong return of the Ottoman Empire to the Persian Gulf, taking advantage of the vacuum created by the withdrawal of Muhammad Ali Pasha.successive successive policies in Europe, and the new Ottoman policy led to a clash with British interests in the Persian Gulf, to begin a new chapter of the British-Ottoman conflict there that had the greatest impact in redistributing influence and loyalties in the Arabian Peninsula.